Involvement of Executive Functions in Idiom Comprehension: A Life-Span Perspective - Agnès Lacroix; Nolwenn Troles; Mélissa Burgevin; Camille Le Bescond; Virginie Laval; Audrey Noël (Brain Sciences)
Objectives—Our aim is to investigate the executive functions involved in idiom comprehension. The understanding of idioms has largely been explored from a developmental perspective. However, little is known about the cognitive processes involved. Recent studies highlight the contributions of working memory and inhibitory control in idiom processing. We investigated executive functions’ implication in idiom comprehension from a life-span perspective. Methods—The participants of this study were aged from 6 years to adulthood (n = 109 participants). An idiom comprehension task and executive tests were administered. Results and Conclusions—The results indicated that idiom comprehension improved across all the age groups tested. Moreover, the involvement of inhibition and cognitive flexibility processes was specific at different ages and particularly involved during adolescence.